2016
DOI: 10.1038/srep37400
|View full text |Cite
|
Sign up to set email alerts
|

Tunable high-performance microwave absorption for manganese dioxides by one-step Co doping modification

Abstract: The frequencies of microwave absorption can be affected by the permanent electric dipole moment which could be adjusted by modifying the crystal symmetry of the microwave absorbing materials. Herein, we corroborate this strategy experimentally and computationally to the microwave absorption of manganese dioxides. Nanosized Co-doped cryptomelane (Co-Cryp) was successfully synthesized by a one-step reaction. The introduction of Co(III) induced a change of crystal symmetry from tetragonal to monlclinic, which cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 64 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…As presented in Figure c, the deconvoluted peaks of Mn 2p 3/2 , at 642.6, 644.3, and 647.6 eV in the case of α‐MnS and at 641.1, 642.6, and 645.6 eV in the case of α‐MnS/rGO, can be ascribed to Mn(II), Mn(III), and Mn(IV), respectively. Similarly, the Mn 2p 1/2 can be deconvoluted to three peaks at 654.2, 655.8, and 657.3 eV, in the case of α‐MnS and at 652.9, 654.3, and 655.6 eV in the case of α‐MnS/rGO, which can be assigned to Mn(II), Mn(III), and Mn(IV), respectively . It can be also noted that the peaks position in α‐MnS/rGO spectra slightly shifted to the lower binding energy values as compared to α‐MnS spectra, which could be affected by the shielding effect of the new neighboring atoms (C, O, and N)…”
Section: Resultsmentioning
confidence: 90%
“…As presented in Figure c, the deconvoluted peaks of Mn 2p 3/2 , at 642.6, 644.3, and 647.6 eV in the case of α‐MnS and at 641.1, 642.6, and 645.6 eV in the case of α‐MnS/rGO, can be ascribed to Mn(II), Mn(III), and Mn(IV), respectively. Similarly, the Mn 2p 1/2 can be deconvoluted to three peaks at 654.2, 655.8, and 657.3 eV, in the case of α‐MnS and at 652.9, 654.3, and 655.6 eV in the case of α‐MnS/rGO, which can be assigned to Mn(II), Mn(III), and Mn(IV), respectively . It can be also noted that the peaks position in α‐MnS/rGO spectra slightly shifted to the lower binding energy values as compared to α‐MnS spectra, which could be affected by the shielding effect of the new neighboring atoms (C, O, and N)…”
Section: Resultsmentioning
confidence: 90%
“…Song et al observed a high-temperature EMI shielding performance higher than 20 dB of β-MnO 2 nanorods in the X-band (8.2–124 GHz). However, the low electrical conductivity and reflection loss of MnO 2 required its doping with polyaniline film, cobalt­(III), and Ni 2+ doping to further enhance its electromagnetic shielding performance. Zhou et al reported a maximum reflection loss ( R L ) of up to −41 dB at 8.7 GHz with a thickness of 1.9 mm for nonstructural hollow urchinlike α-MnO 2 in the presence of a paraffin wax composite.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical transition metal oxide, manganese dioxide (MnO 2 ) has been intensively studied in the fields of catalyst, batteries and electrochemical capacitor electrodes, due to its unique advantages including natural abundance, cheap precursors, easy synthesis, and thermal stability 10 – 12 . Significantly, MnO 2 has been proved to be a competitive candidate for EMW absorptions and shields 13 15 . Nevertheless, the weak electrical conductivity and poor magnetic loss requires morphological tailoring, ion doping or incorporating with conductive components to improve its electrochemical or electromagnetic properties 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%